Heritage uncovered appreciating the Philippines' cultural heritage amidst a highly westernized society, through a promotional video and website about kontra-GaPi and their contemporary ethnic performances - Tongson, Mary Denise L.
As a time where most Filipinos are caught up with art forms and trends that are heavily influenced by the West, our nation's rich cultural heritage is often forgotten and buried deep beneath foreign pop culture. When residing within an urban setting like Metro Manila, it becomes difficult, most especially for younger generations, to appreciate and value the country's ethnic, indigenous music and dance originating from other Filipino communities at distant parts of the archipelago.